Indução metabólica de fungos filamentosos pelas técnicas de co-cultivo, OSMAC e modulação epigenética: produção de metabólitos secundários com atividade neuroprotetora - Geane Pereira de Oliveira (2019)
Fungi kingdom comprises a wide variety of species offering promising sources for the discovery of new bioactive compounds. In this work, co-cultivation, OSMAC and epigenetic modulation techniques were used aiming at inducting the metabolism of five filamentous fungi, Aspergillus chevalieri, Clonostachys regersoniana, Talaromyces calidicanius, Fusarium nygamai and Penicillium sp., for production of secondary metabolites with biological activity. Four experiments were performed using the different approaches in solid and liquid culture media. The extracts were submitted to analysis by HPLC and mass spectrometry with paper spray ionization (PS-MS) to evaluate variation of the metabolic profiles and identification of compounds, as well as acetylcholinesterase inhibitory activity assay. Based on the variations of profiles and activity observed, five co-cultures were performed on larger scale. From the co-culture extracts were isolated six substances, and their structures were elucidated using 1D and 2D NMR techniques, infrared and high resolution mass spectrometry, being identified as Dmannitol (GO-1), echinilin (GO-2), physcion (GO-3) flavoglaucin (GO-4), auroglaucin (GO-5) and tetrahydroauroglaucin (GO-6). GO-2-GO-6 were tested for acetylcholinesterase inhibitory activity and showed IC50 ranging from 62.9 – 190.7 µM. Compound GO-2 also presented preventive (42.66 ± 1.34%) and therapeutic (27.93 ± 1.0%) neuroprotective activities, being therefore a promising substance for the devolpment of drugs to treat neurodegenerative diseases. Compounds GO2 to GO-6 were quantified and GO-5 and GO-6 had their levels increased in the three cultures of the fungus A. chevalieri in relation to the control. PS-MS analysis of the fungal co-culture extracts resulted in the identification of four compounds, linoleic acid, p-coumaric acid, 9-hydroxy-megastigma-3,5,8-trien-7-one-9-O-β-Dglucopyranoside and 9-hydroxyoctadeca-dienoic acid.